2020
DOI: 10.1128/mbio.01969-20
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Next-Generation Sequencing of Nasopharyngeal Specimens Collected from Confirmed and Suspect COVID-19 Patients

Abstract: Metagenomic next-generation sequencing (mNGS) offers an agnostic approach for emerging pathogen detection directly from clinical specimens. In contrast to targeted methods, mNGS also provides valuable information on the composition of the microbiome and might uncover coinfections that may associate with disease progression and impact prognosis. To evaluate the use of mNGS for detecting severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and/or other infecting pathogens, we applied direct Oxford Nanopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
171
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(202 citation statements)
references
References 48 publications
9
171
15
Order By: Relevance
“…1 B). This is in correlation with the host transcriptomics response [ 16 ], where the elicitation of cytokines and other immune responses are higher in IAV treatment and muted during SARS-CoV-2 treatment. As previously reported [ 11 , 12 ], we observed proliferation of betaproteobacteria particularly Pseudomonadales during IAV infection.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…1 B). This is in correlation with the host transcriptomics response [ 16 ], where the elicitation of cytokines and other immune responses are higher in IAV treatment and muted during SARS-CoV-2 treatment. As previously reported [ 11 , 12 ], we observed proliferation of betaproteobacteria particularly Pseudomonadales during IAV infection.…”
Section: Resultsmentioning
confidence: 81%
“…Blanco-Melo et al [ 16 ] reported the unique transcriptional signature in cell lines and nasal washes of ferrets infected with SARS-CoV-2 (strain USA-WA1/2020) and influenza A virus (IAV; pH1N1; A/California/04/2009 strain). The nasal washes are collected from the infected and control animals on specific days and bulk RNA sequencing was performed by Blanco-Melo et al group and the raw data files are deposited in NCBI-SRA (Accession No.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 55 In a similar study, a higher abundance of Propionibacteriaceae and reductions in Corynebacterium accolens was observed in COVID-19 negative patients compared to COVID-19 positive patients. 56 Next-gen immunosequencing performed from blood collected from COVID-19 positive patients as well as recovered patients has been used to generate a library of more than 14 billion B and T-cell receptor sequences to decode host humoral responses generated postinfection. 57 The same study showed that converging IGHV3-driven BCR clusters is mostly responsible for producing SARS-CoV-2 antibodies, whereas interferon (especially IFN-I & III) responses and early CD4+ and CD8+ T cell activation were key factors driving the clonality of T cell receptors.…”
Section: Omics-based Technology Platform For Covid-19 Researchmentioning
confidence: 99%
“…In addition, an increase in certain Clostridial and Pseudomonas opportunistic pathogens have been associated with COVID-19 severity, possibly due to increased risk of secondary bacterial infection [ 21 , 22 , 24 ]. Similarly, infection with SARS-CoV2 may also reduce the diversity of the nasopharyngeal microbiome [ 27 ], and increase abundance of specific genii that can play a role in mucosal immunity, such as Prevotella , the presence of which has been associated with more severe symptoms [ 28 ]. However, data are currently limited to small-scale studies, and more prospective, longitudinal analysis of larger cohorts will be required to unpick the many variables that may contribute to microbial changes.…”
Section: Introductionmentioning
confidence: 99%